1999
DOI: 10.1128/jvi.73.11.9619-9624.1999
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Zoonotic Infection of a Human with Simian Foamy Virus in the Absence of an Intactorf-2Accessory Gene

Abstract: Although foamy viruses (FVs) are endemic among nonhuman primates, FV infection among humans is rare. Recently, simian foamy virus (SFV) infection was reported in 4 of 231 individuals occupationally exposed to primates (1.8%). Secondary transmission to spouses has not been seen, suggesting that while FV is readily zoonotic, humans may represent dead-end hosts. Among different simian species, SFV demonstrates significant sequence diversity within the U3 region of the long terminal repeat (LTR) and 3′ accessory o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 48 publications
0
33
1
Order By: Relevance
“…In the blood, the cellular targets of SFV remain poorly studied. Preliminary studies, performed mostly in small series of chimpanzees, African green monkeys, and in few humans, have shown SFV DNA in lymphocytes, especially CD8+ T cells [25,26]. By studying a larger cohort of humans infected with a gorilla strain of SFV in Cameroon, we demonstrated that CD8+, CD4+ T cells and CD19+ B lymphocytes were preferentially infected, compared to monocytes and NK cells ( Table 1).…”
Section: Sfv Tropismmentioning
confidence: 73%
See 2 more Smart Citations
“…In the blood, the cellular targets of SFV remain poorly studied. Preliminary studies, performed mostly in small series of chimpanzees, African green monkeys, and in few humans, have shown SFV DNA in lymphocytes, especially CD8+ T cells [25,26]. By studying a larger cohort of humans infected with a gorilla strain of SFV in Cameroon, we demonstrated that CD8+, CD4+ T cells and CD19+ B lymphocytes were preferentially infected, compared to monocytes and NK cells ( Table 1).…”
Section: Sfv Tropismmentioning
confidence: 73%
“…SFV DNA loads in this sorted cell population is 1/10 5 cells (in the 7/9 positive samples from AGM) and 1/10 5 cells (in the 3/4 samples from CPZ). b In the study from Callahan et al [25], only one dilution of leucocytes DNA was shown, corresponding to a viral load of >70 SFV DNA copies/10 5 cells, assuming the usual sensitivity of 1 SFV DNA copies/10 5 cells.…”
Section: Hostmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on available data, SFV transmission among humans has not been yet demonstrated. Indeed, only around 40 family members (mostly spouses) of men infected by SFV have been studied and scored negative Callahan et al, 1999;Heneine et al, 1998;Switzer et al, 2004;Boneva et al, 2007) suggesting that SFV transmission does not occur frequently through sexual contacts or saliva exposure. The persistence of infectious virus in PBMCs, and the identification of infected blood donor (CDC study conducted in North America (Boneva et al, 2002)) had raised safety concerns regarding a potential viral transmission through blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups also reported genetic modifications including deleterious mutations in the Bet accessory gene in one SFVinfected human (Callahan et al, 1999). Some other features were also reported in humans infected with FVs, although they are probably not specific to human infection.…”
Section: Fv Restriction In Humansmentioning
confidence: 95%